2001
DOI: 10.1073/pnas.012608399
|View full text |Cite
|
Sign up to set email alerts
|

Sequence analysis of mouse vomeronasal receptor gene clusters reveals common promoter motifs and a history of recent expansion

Abstract: We have analyzed the organization and sequence of 73 V1R genes encoding putative pheromone receptors to identify regulatory features and characterize the evolutionary history of the V1R family. The 73 V1Rs arose from seven ancestral genes around the time of mouse-rat speciation through large local duplications, and this expansion may contribute to speciation events. Orthologous V1R genes appear to have been lost during primate evolution. Exceptional noncoding homology is observed across four V1R subfamilies at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
64
0
3

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(71 citation statements)
references
References 44 publications
(49 reference statements)
4
64
0
3
Order By: Relevance
“…L1 density differs between species, so it would be interesting to see how V1R repertoire size correlates with L1 density. After the procedure of Lane et al (22), we found that 21% of the DNA sequences in the genomic regions harboring dog V1R genes are L1 elements, lower than the corresponding density (40%) in the mouse V1R loci (22) or the average density (25%) in the mouse genome (56). The L1 density of the genomic regions containing cow V1R genes is also 21%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…L1 density differs between species, so it would be interesting to see how V1R repertoire size correlates with L1 density. After the procedure of Lane et al (22), we found that 21% of the DNA sequences in the genomic regions harboring dog V1R genes are L1 elements, lower than the corresponding density (40%) in the mouse V1R loci (22) or the average density (25%) in the mouse genome (56). The L1 density of the genomic regions containing cow V1R genes is also 21%.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is unknown what factors have promoted the dramatic expansions in rodents but have only allowed limited expansion in cows and virtually no expansion in dogs. Lane and colleagues (22,55) suggested that the V1R gene duplications in rodents were mediated by L1 repetitive elements. These elements, which are known to have been active in rodents around the time of the mouse-rat divergence, densely populate the regions of the mouse and rat genomes where V1Rs are located.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, the requirement of M10 molecules for the transport of some V2Rs to cell membranes is probably a rodent-specific phenomenon and the use of ESPs as potentially V2R-recognizing pheromones are also rodent-specific. Previous phylogenetic analyses of V1R and V2R genes showed that only a few one-to-one orthologous gene pairs exist even between closely related species such as the mouse and rat, due to rapid birth and death of vomeronasal receptor genes (Lane et al 2002(Lane et al , 2004Grus and Zhang 2004;Yang et al 2005). Interestingly, similar patterns are found in the M10 and ESP genes.…”
Section: Evolution Of Protein Families That Interact With V2rsmentioning
confidence: 99%
“…Their natural ligands are highly diverse, comprising biogenic amines (such as adrenaline, dopamine, histamine, and serotonin), peptides (such as angiotensins, bradykinins, somatostatins, and melanocortins), large proteins (such as luteinizing hormone, follicle-stimulating hormone, and thyroid-stimulating hormone), nucleosides and nucleotides (adenosine, ATP, UTP, and ADP), lipids and eicosanoids (such as leukotrienes, prostaglandins, and cannabinoids) and photons. Moreover, it has also been suggested that there exist over 900 genes for olfactory receptors in the human genome [5]. A large number of these are pseudogenes and the speci¢c roles of only a few of the receptors are known.…”
Section: Introductionmentioning
confidence: 99%